Theories of adaptation and functional systems in the development of knowledge in the fi eld of preparation of athletes - Владимир Платонов (National University of Physical Education and Sport of Ukraine, 2017)
The paper analyzes the relationship and complementarity of the theory of adaptation and the theory of sports training. Potential of the theory of adaptation is demonstrated for the development of knowledge in the field of training athletes. The types of adaptation are described, and the issues of adaptational adjustments of the athlete's body are examined depending on the size and nature of the loads. Multistage and variable nature of adaptive responses typical of sports are demonstrated along with the importance of phenomena such as over-adaptation, de-adaptation, and readaptation. Relationships between adaptation responses, formation and development of functional systems, and characteristic of the concept of «functional preparedness» are discussed.